2015
DOI: 10.1039/c5ra08298f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular self-assembly of novel thermo-responsive double-hydrophilic and hydrophobic Y-shaped [MPEO-b-PEtOx-b-(PCL)2] terpolymers

Abstract: Nonlinear amphiphilic block copolymer architectures with precisely controlled structures bring new challenges to biomedical materials research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Synthesis strategies for Y-shaped AB 2 miktoarm polymers include atom transfer radical polymerization (ATRP), 35,36 opening polymerization (ROP), [37][38][39] and "click" reaction 40 as well as versatile combinations of different polymerization methods, including ATRP/ROP, 41,42 reversible addition-fragmentation chain transfer (RAFT) polymerization/ROP, 43 ROP/click, 44 ATRP/ ROP/click, 45 living cationic polymerization/ROP, and anionic polymerization/ROP combination. 46,47 Meanwhile, self-assembly of Y-shaped AB 2 miktoarm polymers in solution also has been investigated in detail. Experimental results showed that selfassembly in solution of Y-shaped AB 2 miktoarm polymers is different from that of their linear counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis strategies for Y-shaped AB 2 miktoarm polymers include atom transfer radical polymerization (ATRP), 35,36 opening polymerization (ROP), [37][38][39] and "click" reaction 40 as well as versatile combinations of different polymerization methods, including ATRP/ROP, 41,42 reversible addition-fragmentation chain transfer (RAFT) polymerization/ROP, 43 ROP/click, 44 ATRP/ ROP/click, 45 living cationic polymerization/ROP, and anionic polymerization/ROP combination. 46,47 Meanwhile, self-assembly of Y-shaped AB 2 miktoarm polymers in solution also has been investigated in detail. Experimental results showed that selfassembly in solution of Y-shaped AB 2 miktoarm polymers is different from that of their linear counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The paclitaxel release is sustained in all tested conditions; however, it is substantially accelerated at temperatures of 37 (>90% released in 48 h) and 40 • C (>90% released in 24 h) when compared to 25 • C (>80% released in 48 h). These results suggest that at temperatures closer to the LCST (37 • C), the BC3 NPs start to become physically destabilized (temperature-triggered activation-de-swelling aggregation) [75,76], thus accelerating the release of the anticancer drug. This effect is most pronounced at a temperature above the LCST, where the PTX is released completely within the first 24 h at 40 • C, mimicking, for instance, temperatures in the range used for hyperthermia treatment [46,77].…”
Section: Paclitaxel-loaded Bc3 Nanoparticles and Paclitaxel Releasementioning
confidence: 95%
“…The transformation of living cationic polymerization ‐Ŧ‐ ROP has been reported in 2015 by Petrova et al . This group described a successful three‐step synthesis of double‐hydrophilic and hydrophobic biocompatible triblock terpolymers containing PEO, poly(2‐ethyl‐2‐oxazoline) (PEtOx) and poly(ε‐caprolactone) (PCL) segments by a combination of living cationic polymerization and anionic ring opening polymerization (ROP).…”
Section: Transformations From Living Cationic Polymerizationmentioning
confidence: 99%